2000
DOI: 10.1002/1096-9845(200012)29:12<1845::aid-eqe995>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wind effects on a supertall building based on full-scale measurements

Abstract: SUMMARYThis paper describes the results obtained from the full-scale measurements of wind e ects on a 70-storey building in Hong Kong. The building which has a height of approximately 370 m is the second tallest structure in Hong Kong. The ÿeld data such as wind speed, wind direction and wind-induced acceleration responses have been measured since 1995 including the close passage of two typhoons; typhoon Sally and typhoon Kent. Detailed analysis of the ÿeld data is conducted. The full-scale measurements are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 8 publications
0
33
0
Order By: Relevance
“…More sophisticated friction laws, even state-dependent dynamic friction laws, may be needed. A comprehensive review of friction, in particular in dynamic context, can be found in [45].…”
Section: Further Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More sophisticated friction laws, even state-dependent dynamic friction laws, may be needed. A comprehensive review of friction, in particular in dynamic context, can be found in [45].…”
Section: Further Discussionmentioning
confidence: 99%
“…Considering five DOFs for each node, which are the two horizontal translational and three rotational DOFs, a total number of 185 DOFs are included. The damping ratio of the structure was assumed to be 0.004 [44,45]. The layout of the model [46] is shown in Figure 6.…”
Section: Shm System and Benchmark Model Of The Canton Towermentioning
confidence: 99%
“…Considering five DOFs for each node, which are the two horizontal translational and three rotational DOFs, a total number of 185 DOFs are included. The damping ratio of the structure was assumed to be 0.004 [44,45]. The layout of the model [46] is shown in Figure 6.…”
Section: Shm System and Benchmark Model Of The Canton Towermentioning
confidence: 99%
“…For instance, Brownjohn et al (1998) established a long-term monitoring program for a 280 m high 65-story office tower in Singapore to monitor structural dynamic responses and track structural performance during and after construction. A full-scale measurement of acceleration responses on a 70-story building in Hong Kong under strong typhoons was conducted (Li et al 2000).…”
Section: Introductionmentioning
confidence: 99%